Various Layers in Social Psychology - Mehrad, Aida; Cordic, Sarah; Crecelius, Grace; Procise, Woods; Wagner, Kylie (UIN Sunan Kalijaga, 2024)
Understanding humans through social influence is always needed. Through an analysis of specific topics of social psychology, a bridge between issues can be created. This research aims to understand the various layers in social psychology using secondary data. The methodology used in this study is qualitative research, particularly literature review. The subject of this study is some literatures in databases, and other scholarly articles to use as supporting evidence for this work about the study of social psychology. The results provide understanding of layers on social psychology including how individuals interact and function in the day-to-day lives. Human can learn how to better recognize the information process happening in their brains and how to manipulate it in different social situations. The depth of how human relate to each other, and their surroundings is seen through social psychology's